pH-dependent formation of oriented zinc oxide nanostructures in the presence of tannic acid - Nurul Akmal, Che Lah; Aqilah, Kamaruzaman; Trigueros, Sonia (MDPI AG, 2020)
To crucially comprehend the relaying factors behind the growth mechanism of ZnO nanostructures, the needs to understand the cause of preferences in the enhancement of desired physicochemical properties are essential. The particular oriented attachment (OA) is believed to become the cause of the classical growth pattern of ZnO nanostructures which is mainly controlled by the Ostwald ripening (OR) process. In the present work, the concerns over the systematic changes in size and the morphological surface of ZnO nanostructures upon exposure to tannic acid (TA) prepared by drop-wise method turns the particles to different surface adjustment state. Here, we assessed the TA capping ability and its tendency to influence the OA process of the ZnO nanostructures. The detailed process of the growth-based TA system via transmission electron microscopy (TEM), scanning electron microscopy (SEM), and FFT autocorrelation revealed the pH effect on their physical properties which proved the transition surface properties state of the particles from rough to smooth states due to oriented attachment. For pure ZnO nanostructures, the surface is almost smooth owing to the strong bonding particles which are then changed to coarsened surface structures upon the introduction of TA. Strong surface adsorption of Zn cations and phenol ligands mediated the agglomerated nanocrystals, surprisingly with smaller nanostructures dimension.